Asses The Impact Of Cyber Crime Mitigation Strategies On Islamic Banks In Bandar Lampung City - Muhammad Varhisky Febriawan; Eogenie Lakilaki; Dwiki Ariefandri; Ryan Aditya Saputra; Panca Wijaya; Desta Manikam (Jurnal Ekuilnomi, 2024)
It is of the utmost importance to cultivate customer trust in Islamic banking. The effective management of technology in the banking sector has the potential to significantly influence customer trust and loyalty. The objective of this study is to investigate the influence of cyber security on customer loyalty, with trust as a mediating variable. The sampling was conducted using the Lemeshow method, with a total of 96 respondents. The data were analysed using the structural equation modelling with partial least squares (SEM-PLS) method. The research findings demonstrate that cyber-handling has a positive and significant influence on customer loyalty and trust, respectively. The implications of these findings emphasise the necessity for banks to reinforce their cybersecurity strategies in order to maintain customer loyalty and to develop further innovations with the objective of increasing trust, which will ultimately contribute to customer loyalty. In conclusion, effective cyber management and increased customer trust are pivotal in retaining and enhancing banking customer loyalty